2022
DOI: 10.1177/09720634221076964
|View full text |Cite
|
Sign up to set email alerts
|

Policy Implications of the Concept of Technological Catch-Up for the Management of Healthcare Sector in Developing Countries

Abstract: The concept of technological catch-up can be used as a theoretical platform to design policies for the management of the healthcare sector in developing countries. In this article, initially, the factors affecting a technological catch-up process were collected through a conceptual literature review and prioritised using a fuzzy Delphi survey. The interdependences among important contributory factors were investigated as well. They were then used to create some policy recommendations for the management of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 101 publications
1
0
0
Order By: Relevance
“…18 Equally, inadequate data processing by software can lead to ineffective analysis and hinder significant conclusions for decision-making, consequently impacting information use. 19 Furthermore, the outcomes of this study align with those of a study done in India, which underscores that enhancing skills in analyzing, and interpreting, as well as decision-making encourages information use. 20 In their study, they revealed that a properly designed HMIS, coupled with appropriate training following internationally recognized practices, contributes to the data quality necessary for informed decisions.…”
Section: Discussionsupporting
confidence: 69%
“…18 Equally, inadequate data processing by software can lead to ineffective analysis and hinder significant conclusions for decision-making, consequently impacting information use. 19 Furthermore, the outcomes of this study align with those of a study done in India, which underscores that enhancing skills in analyzing, and interpreting, as well as decision-making encourages information use. 20 In their study, they revealed that a properly designed HMIS, coupled with appropriate training following internationally recognized practices, contributes to the data quality necessary for informed decisions.…”
Section: Discussionsupporting
confidence: 69%